Mass inflow rate into the Central Molecular Zone: observational determination and evidence of episodic accretion - Sormani, Mattia C.; Barnes, Ashley T. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. It is well known that the Galactic bar drives a gas inflow into the Central Molecular Zone, which fuels star formation, accretion on to the central s
Gesehen am 04.02.2019